Climate Change and Economic Growth Prospects for Malawi: An Uncertainty Approach. (August 2014) - Arndt, Channing; Schlosser, Adam; Strzepek, Kenneth; Thurlow, James
Abstract : Malawi confronts a growth and development imperative that it must meet in a context characterised by rising temperatures and deep uncertainty about trends in precipitation. This article evaluates the potential implications of climate change for overall growth and development prospects in Malawi. We combine climate, biophysical and economic models to develop a structural analysis focused on three primary impact channels: agriculture, road infrastructure and hydropower generation. We account explicitly for the uncertainty in climate forecasts by exploiting the best available information on the likely distribution of climate outcomes. We find that climate change is unlikely to substantially slow overall economic growth over the next couple of decades. However, assuming that global emissions remain effectively unconstrained, climate change implications become more pronounced over time. Reduced agricultural yields and increased damage to road infrastructure due to increased frequency and intensity of extreme events are the principal impact channels. Owing to the potential for positive impacts in the near term, the net present value of climate impacts from 2007 to 2050 (using a 5% discount rate) can be positive or negative with an average loss of about USD 610 million. The main implication of our findings is that Malawian policy makers should look to exploit the coming decade or two as these represent a window of opportunity to develop smart and forward looking adaptation policies. As many of these policies take time to develop, implement, and then execute, there is little cause for complacency.